Organic semiconductor devices for X-ray imaging - Blakesley, James C.; Keivanidis, Panagiotis E.; Campoy-Quiles, Mariano; Newman, Christopher R.; Jin, Y.; Speller, Robert; Sirringhaus, Henning; Greenham, Neil C.; Nelson, Jenny; Stavrinou, Paul N. (My University, 2007)
We investigate the potential for replacing inorganic semiconductors with polymeric semiconductors in medical X-ray imaging applications. Polymeric semiconductors are soft and can be fabricated using techniques such as spin coating and jet printing, leading to reductions in fabrication costs for large-area arrays, easy integration of heterostructures and composite materials and the possibility of using flexible substrates. By using a combined cascaded linear systems and Monte-Carlo model to simulate the imaging system, we establish a set of semiconductor requirements for a feasible flat-panel imager (FPI). We have fabricated photodiodes and thin-film transistors (TFTs) out of a variety of polymer materials. Polymer photodiodes coupled to phosphor screens have shown a response to X-ray radiation with a good efficiency. Both transistors and photodiodes were sufficiently radiation hard for use in clinical imaging conditions. A composite phosphor-polymer material has been fabricated and has been found to be compatible with polymeric photodiodes. The composite material can be fabricated within a structure as part of the semiconductor fabrication process. © 2007 Elsevier B.V. All rights reserved.
Keywords: Organic semiconductors; Conjugated polymers; Digital radiography